Experiências, Práticas e Discursos num Contexto de Pesca - Domingues, Adelina Gomes (Trabalhos de Antropologia e Etnologia, 2020)
From an ethnography among people interacting with maritime environment (fishermen and harvesters of clam) in Seixal (Tagus estuary, Portugal), we reflect upon local groups agency and its possible connections with other scales, aiming to understand the interrelationships human beings and environment. Analyzing life and work memories, practices, perceptions and perspectives of individuals and families, continuities, breaks and returns to fishing arise. Those oscillations result from different social, economic, local and global conjunctures. From experiences and discourses of those who act on the environment, we glimpse survival strategies and choices throughout lives of precarious work and "crisis".